Beacons: A tool for 21st Century teaching and learning? - Charles Atherton (Association for Learning Technology, 2019)
Beacon technology was developed by Apple in 2013, and its initial use in secondary education has generated much enthusiastic descriptive and web-based claims of its potential. However, not only is there a paucity of academic study on its use in the classroom, but none of these claims have been critiqued. Additionally, if teachers are to use the technology in their pedagogy, they should know how to do so, theoretically and practically. This paper reports on research that was jointly conducted with a Year 10 Science teacher in an independent secondary school in the UK. Using an action research methodology, the research employed qualitative methods, such as observations, interviews and focus groups, to assess, from both the teacher's and pupils' perspectives, what affordances beacons have for pedagogy and what limitations constrain their use in practice. The results illustrated that beacons have several affordances for both teachers and pupils that, collectively, support constructivist approaches to learning. However, they also revealed technological and user limitations that affect both the use and efficacy of beacons in practice. Further research is needed to quantify the effect of beacons on pupils' learning. Longitudinal research is needed to verify these findings over time and with a larger sample.